2020
DOI: 10.1590/1983-21252020v33n104rc
|View full text |Cite
|
Sign up to set email alerts
|

Grasses and Legumes as Cover Crops Affect Microbial Attributes in Oxisol in the Cerrado (Savannah Environment) in the Northeast Region1

Abstract: The cover crop straw may cause changes in the microbial activity and population, with repercussions on environmental changes and on the C and N dynamics, providing important information for the planning of adequate land use in the Cerrado. The objective of this study was to evaluate the effect of straw of cover crops on the soil microbial attributes and quality of organic matter. Experimental units consisted of 100 g of sieved soil placed in small plastic cups mixed with straw from cover plants. Treatments wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Cover crops are well known for their positive effects on soil such as erosion processes, physical properties, organic matter, microbial population, nutrient cycling, potassium (K + ) and nitrate (NO 3 – ) leaching and weed populations (Almeida et al., 2018; Amorim et al., 2020; Surekha et al., 2006; Tardy et al., 2017). Several cover crops have been researched and used in tropical conditions; among these, forage grasses are the most studied.…”
Section: Introductionmentioning
confidence: 99%
“…Cover crops are well known for their positive effects on soil such as erosion processes, physical properties, organic matter, microbial population, nutrient cycling, potassium (K + ) and nitrate (NO 3 – ) leaching and weed populations (Almeida et al., 2018; Amorim et al., 2020; Surekha et al., 2006; Tardy et al., 2017). Several cover crops have been researched and used in tropical conditions; among these, forage grasses are the most studied.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the soils evaluated are native Cerrado, whose characteristic is low fertility, with high values of attributes linked to acidity and aluminum, and low in basic cations and phosphorus (Amorim et al, 2020), thus we can justify the contrasting result between the mentioned chemical attributes and iBt, since there is a need for an adequate pH and nutrient concentrations for a satisfactory development of microorganisms (Medhi et al, 2017), including Bt, as reported in Rabinovitch et al (2017). Furthermore, for a good conditions for bacterial growth includ temperature and pH, so in low value of pH, that represent high levels of H+Al and Al in soils of Cerrado could be explain the results founded (Kalsoom et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Grass-Legume Seeding: A Sustainable Approach towards Reclamation of Coalmine Degraded… DOI: http://dx.doi.org/10.5772/intechopen.99741 A grass-legume association potentially accumulates high quality organic substrates in soil with soil organic carbon (SOC) and N pool accretion and promoting beneficial soil micro-organisms [53][54][55]. The difference in the chemical composition of grass-legume mixture incorporated in soil shifts the nutrient cycling via mineralization which stimulated the soil microbial activities [56]. Soil microorganisms are a necessary link between plant-soil interaction for productivity, nutrient availability and cycling thus, legumes are one of the necessary components to increase soil microbial activity accelerating the process of ecological restoration in mined areas [29].…”
Section: Soil Fertilitymentioning
confidence: 99%